Financial analysis tools for assessing the investment attractiveness of agricultural projects in the United States - Viktoriia Lezhanina (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This article focuses on the analysis and practical application of financial tools aimed at evaluating the investment attractiveness of agricultural projects in the United States. In a context of declining domestic investment and a volatile business climate, agricultural enterprises require accurate assessments of their internal reserves and creditworthiness. The relevance of this study is driven by the need to identify effective financing mechanisms and enhance the competitiveness of farming operations facing additional pressure from seasonal price fluctuations and technological transformation. The novelty of the research lies in a detailed examination of the interrelation between depreciation monitoring methods, liquidity analysis, capital structure, and profitability. The study presents comparative approaches to long-term lending and solvency assessment and draws on sources addressing trends in investment flows, challenges related to fixed asset renewal, the specifics of banking activity, and external support programs. Particular attention is given to risk assessment, including potential capital outflows and insufficient diversification of financing channels. The study aims to identify optimal strategies for strengthening the financial stability of agricultural enterprises. A comparative method and financial statement analysis were applied to achieve this goal. The conclusion outlines a sequence of steps enabling an objective forecast of project profitability. This article will be of interest to investors, enterprise managers, and specialists in agricultural management.